Chiari malformation - modern aspects of diagnostics and treatment - S. N. Larionov; V. A. Sorokovikov; V. E. Potapov (Acta Biomedica Scientifica, 2013)
The review presents modern ideas about morphology of afterbrain malformations - Chiari, type I. Main criteria of introscopic diagnistics of Chiari malformation of type I and of combined anomalies of development of craniovertebral articulation are discussed. The theories of pathogenesis of craniocervical dysplasias of afterbrain and development of intramedullary cavities are presented. The criteria of differential diagnostics of hydromyelia and syringomyelia and also modern methods of surgical treatment of bone and neural dysplasias are determined. Main clinical features of the course of disease that appears in mosaic picture of cerebellum affection, caudal group of craniocerebral nerves, medulla, brain hemispheres and spine cord are revealed, the characteristics of the mostfrequent syndromes is given. The reconstruction of anatomic symmetry of cone and neural structures of craniocervical articular and restoration of circulation of cerebrospinal fluid through outcomes of the IV ventricle guarantees favorable results of treatment. Promptly and adequately performed operation at the pathology of afterbrail allows to prevent development of irreversible and low-curable morphofunctional defects of neural system.